Unleashing the potential of high-throughput sequencing for plant virus and viroid detection in Mexico - Pacheco-Dorantes, Carolina; Tovar-Pedraza, Juan Manuel; Ochoa-Martínez, Daniel Leobardo; González-Garza, Ramiro; Diaz-Lara, Alfredo (Frontiers in Microbiology, 2025)
High-throughput sequencing (HTS) has revolutionized plant virology in Mexico by enhancing the detection and characterization of plant viruses and viroids. This technology has contributed to identifying previously neglected pathogens affecting key crops such as corn, beans, and tomato. The use of HTS has also revealed the presence of mixed viral infections, highlighting the complexity of plant viromes within agricultural ecosystems. Furthermore, metagenomic studies have demonstrated the role of water sources as reservoirs for plant viruses, underscoring the urgent need for improved management strategies. Despite its advantages, the widespread adoption of HTS faces challenges, including high costs, the need for bioinformatics expertise, and infrastructure limitations. Supporting collaborations between research institutions and regulatory agencies is crucial to integrating HTS into routine phytosanitary programs. Future research should aim to expand HTS applications to include epidemiological monitoring, resistance breeding, and the development of sustainable management strategies to mitigate the impact of emerging plant viruses in Mexico.